Properties of materials considered for improvised masks. Issue 4 (3rd April 2021) - Rogak, Steven N.; Sipkens, Timothy A.; Guan, Mark; Nikookar, Hamed; Vargas Figueroa, Daniela; Wang, Jing
Abstract: During a pandemic in which aerosol and droplet transmission is possible, such as the COVID-19 pandemic of 2020, the demand for face masks that meet medical or workplace standards can prevent most individuals from obtaining suitable protection. Cloth masks are widely believed to impede droplet and aerosol transmission, but most are constructed from materials with unknown filtration efficiency, airflow resistance and water resistance. Here we provide data on a range of common fabrics that might be used to construct masks, complimenting existing studies by largely considering particles in the micron range (a plausible challenge size for human generated aerosols). None of the materials were suitable for N95 masks, but many could provide useful filtration (>90%) of 3 micron particles, with low pressure drop. These were: nonwoven sterile wraps, dried baby wipes and some double-knit cotton materials. Decontamination of N95 masks using isopropyl alcohol produces the expected increase in particle penetration, but for 3 micron particles, filtration efficiency is still well above 95%. Tightly woven thin fabrics, despite having the visual appearance of a good particle barrier, had remarkably low filtration efficiency and high pressure drop. The better material structures expose individual fibers to the flow while the poor materials may have small fundamental fibers but these are in tightly bundled yarns. Despite the complexity of the design of a very good mask, it is clear that for the larger aerosol particles, any mask will provide substantial protection to the wearer and those around them. Copyright © 2021 American Association for Aerosol Research